Power, Justice and Citizenship. - McBain, Darian (BRILL, 2019)
Who holds the power when considering environmental justice and global citizenship? Citizenship is felt most strongly with those that we are closely connected with, either by physicality or ideology. In a world where connectivity is changing our perception of citizenship we consider who holds the power to bring about change. This volume looks at the role played by various actors seeking or discouraging environmental justice. We consider the role of actors ranging from individual citizens working at a grassroots level through to governments and the media. We also look at the role that education has to play in environmental justice from the classrooms to policy directions at the United Nations. Theories of environmental justice and citizenship are explored in conjunction with case studies to provide a thought-provoking look at power relationships for environmental justice in the start of the 21st century.